Case Report of a Rare Complication of Open-Heart Surgery Masquerading as a Gunshot Wound: An Autopsy Diagnosis. (June 2015) - Kak, Ipshita; Nair, Vidhya
Abstract : Introduction: Poststernotomy mediastinitis is a rare feared sequelae of open-heart surgery with low incidence of 1% to 3% but a high mortality rate (10%–35%). Poststernotomy mediastinitis can in uncommon instances give rise to sternocutaneous fistulas in 0.25% to 10% of cases. Although scant reports have documented prosthetic valve endocarditis occurring in a setting of deep sternal wire infections, it is an infrequent but well-documented fatal complication of valvular replacement surgery. Case Report: A 52-year-old male smoker with aortic valve replacement (2011), on Coumadin and Monocor, was found dead on September 2013 with a hole along a surgical scar over the sternum, masquerading as a gunshot wound. Chest radiograph revealed no foreign body, and no evidence of homicidal/suicidal or accidental cause was found at autopsy. Examination revealed a chronic fistulous tract from a deep sternal wire infection to the skin, in addition to a chronic sinus tract eroding into the root of the aorta with recent prosthetic valve endocarditis. Discussion: To our knowledge, this is the first case report documenting poststernotomy mediastinitis causing a simultaneous occurrence of sternocutaneous fistula and prosthetic valve endocarditis. Either of these 2 exceptional but lethal complications would have sufficed as the cause of death.